Implementation of QR Code and Digital Signature to Determine the Validity of KRS and KHS Documents - Rochman, Fatich Fazlur; Raharjana, Indra Kharisma; Taufik, Taufik (Universitas Negeri Semarang, 2017)
Universitas Airlangga students often find it difficult to verify the mark that came out in the Kartu Hasil Studi (KHS) is called Study Result Card or courses taken in the Kartu Rencana Studi (KRS) is called Study Plan Card, if there are changes to the data on the system used Universitas Airlangga. This complicated KRS and KHS verification process happened because the KRS and KHS documents that owned by student is easier to counterfeit than the data in the system. Implementation digital signature and QR Code technology as a solution that can prove the validity of KRS or KHS. The KRS and KHS validation system developed by Digital Signature and QR Code. QR Code is a type of matrix code that was developed as a code that allows its contents to be decoded at high speed while the Digital Signature has a function as a marker on the data to ensure that the data is the original data. The verification process was divided into two types are reading the Digital Signature and printing document that works by scanning the data from QR Code. The application of the system is carried out were the addition of the QR Code on KRS and KHS, required a readiness of human resources.